Monitoring Extracellular Vesicle Cargo Active Uptake by Imaging Flow Cytometry - Ofir-Birin, Yifat; Abou karam, Paula; Rudik, Ariel; Giladi, Tal; Porat, Ziv; Regev-Rudzki, Neta (Frontiers in Immunology, 2018)
Extracellular vesicles are essential for long distance cell–cell communication. They function as carriers of different compounds, including proteins, lipids and nucleic acids. Pathogens, like malaria parasites (Plasmodium falciparum, Pf), excel in employing vesicle release to mediate cell communication in diverse processes, particularly in manipulating the host response. Establishing research tools to study the interface between pathogen-derived vesicles and their host recipient cells will greatly benefit the scientific community. Here, we present an imaging flow cytometry (IFC) method for monitoring the uptake of malaria-derived vesicles by host immune cells. By staining different cargo components, we were able to directly track the cargo’s internalization over time and measure the kinetics of its delivery. Impressively, we demonstrate that this method can be used to specifically monitor the translocation of a specific protein within the cellular milieu upon internalization of parasitic cargo; namely, we were able to visually observe how uptaken parasitic Pf-DNA cargo leads to translocation of transcription factor IRF3 from the cytosol to the nucleus within the recipient immune cell. Our findings demonstrate that our method can be used to study cellular dynamics upon vesicle uptake in different host–pathogen and pathogen–pathogen systems.